Karakteristik Growol yang Dibuat dengan Variasi Varietas Ubi Kayu (Manihot esculenta Crantz) dan Lama Fermentasi - Sandi Afrianto; Chatarina Wariyah (agriTECH, 2020)
Growol is a staple food made from processed cassava through fermentation, washing, pressing, and chopping. It is beneficial to health due to its lactic acid bacteria content. The problem was that producers always mix different cassava varieties, and varied fermentation time. Meanwhile, each cassava has different composition, especially their starch content. The fermentation time was not constant which ranges between 2-4 days. Furthermore, the typical sour taste and lactic acid bacteria content are determined by the length of this period. Therefore, this study aimed to evaluate the effect of cassava varieties and fermentation time on the chemical properties, total lactic acid bacteria (LAB), and the preference level of growol. The cassava used in this study were Meni, Ketan, and Lanting varieties, with fermentation time ranging between 2-4 days. Each sample were analyzed to determine moisture content, starch, and amylose. Furthermore, the fermented cassava that has been washed and pressed, was steamed for 15 minutes. Therefore, the resulted growols were analyzed to determine their moisture content, pH, titratable acidity, total LAB, and preference level using hedonic test method. The results showed the starch content were not significantly different, but the chemical properties was affected by the fermentation time (moisture content, amylose, titratable acidity), total LAB and preference level. Furthermore, the acceptable growols were made from Meni variety with fermentation time ranging between 2-4 days, or Ketan and Lanting varieties with 2 days fermentation. However, based on the lactic acid bacteria content, growol should be made with Meni variety with 4 days fermentation process, which had moisture content of 60.31 ± 0.21%, titratable acidity of 0.40 ± 0.05% and lactic acid bacteria content of 1.5x106 cfu/g.